Hydroacoustic survey on fish spatial distribution in the early impoundment stage of Yuwanghe Reservoir in southwest China - Luo, Bin; Zhou, Xianjun; Zhang, Chaoshuo; Bao, Jianghui; Mei, Feng; Lian, Yuxi; Zhang, Dongxu; Hu, Shaoqiu; Guo, Longgen; Duan, Ming (Frontiers in Marine Science, 2023)
Understanding the fish community structure and spatial distribution characteristics is essential for appropriate reservoir fishery management, especially in the early impoundment stage of the reservoir, which could help in obtaining basic data and performing artificial adjustments to biological communities. On the basis of this concept, we conducted a survey of the fish community and distribution at the newly constructed reservoir in southwest China by using a combination of methods, including hydroacoustic survey and fish sampling. Fish sampling showed a single fish community structure (six species belonging to four families) assembled in the reservoir, and the dominant species was Pseudorasbora parva which accounted for 98.79% of the fish population. In the hydroacoustic survey, the average fish density was 318.7 ± 256.1 individuals/1,000 m2. Irregular distribution of the fish was observed in the horizontal direction. The fish densities in the head area, middle area, and tail area of the reservoir were 168.5 ± 60.1, 306.8 ± 124.7, and 696.4 ± 288.9 individuals/1,000 m2, respectively, which showed a trend of increase in fish density with an increase in distance from the dam. More than 97.3% of the fish in the vertical direction were distributed in the water layer of depth 0 to 12 m. The average total length of fish was 75.4 mm, and the mean fish biomass in the reservoir was approximately 984.8 g/1,000 m2. According to Pearson correlation analysis, the main factors affecting the spatial distribution of fish were water depth, water temperature, dissolved oxygen, total nitrogen, and plankton density. Our results suggested that the fish community structure should be adjusted by releasing native carnivorous fish to control the abundance of small fish. Moreover, filter-feeding fish such as silver carp and bighead carp should be released in the reservoir to control the plankton community; this will enable the maintenance of the reservoir ecosystem in a healthy state while increasing the economic benefits to the local area.